2015
DOI: 10.1101/025890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sampling the conformational space of the catalytic subunit of human γ-secretase

Abstract: 17Human γ--secretase is an intra--membrane protease that cleaves many different 18 substrates. Aberrant cleavage of Notch is implicated in cancer, while abnormalities in 19 cutting amyloid precursor protein lead to Alzheimer's disease. Our previous cryo--EM 20 structure of γ--secretase revealed considerable disorder in its catalytic subunit 21 presenilin. Here, we introduce an image classification procedure that characterizes 22 molecular plasticity at the secondary structure level, and apply this method to id… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
267
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(282 citation statements)
references
References 50 publications
(8 reference statements)
15
267
0
Order By: Relevance
“…The C-terminal part of the coiled coil domain showed poor density, indicating a local structural heterogeneity. Therefore, we performed a focused 3D classification with density subtraction in order to improve the density of the coiled coil domain 50 . In this approach, only the density corresponding to the coiled coil domain was kept in each particle image by subtracting the density for all other parts including the nanodisc from the original particles.…”
Section: Methodsmentioning
confidence: 99%
“…The C-terminal part of the coiled coil domain showed poor density, indicating a local structural heterogeneity. Therefore, we performed a focused 3D classification with density subtraction in order to improve the density of the coiled coil domain 50 . In this approach, only the density corresponding to the coiled coil domain was kept in each particle image by subtracting the density for all other parts including the nanodisc from the original particles.…”
Section: Methodsmentioning
confidence: 99%
“…Masked 3D classification procedure 56 was performed using RELION 1.4 to improve the densities in the more flexible regions of our full-length TRPV2 structure. A map of the TM region with the MNG detergent belt was generated using the TRPV2 refined model of the TRPV2 cytoplasmic domains and the split map feature in UCSF Chimera.…”
Section: Methodsmentioning
confidence: 99%
“…The focused classification and refinement approaches (7,8) have been used for two primary purposes: sorting out localized structural heterogeneity among particles (9,10) and improving feature resolvability of flexible domains through local refinement (11,12). These molecular machines frequently are composed of multiple protein subunits that can generate correlated and/or uncorrelated motions (13), and no experimental technique has yet captured the atomic structures of individual subunits within a single molecular machine in solution.…”
mentioning
confidence: 99%
“…However, these studies have not revealed any heterogeneity among the protomers in each oligomer. Here we used a 3D classification strategy for cryo-EM data (10) to investigate structural heterogeneity among chemically identical subunits and their conformational variation and correlation in a single GroEL.…”
mentioning
confidence: 99%